(3JSHjY GdbUjOI GdHQOjIs - (3YHO Gddg Hf YeQ Hf eMeO, J(B685(3g`s ((3YKeGf Hf MSjf Hf CMeOs)
(3ChdgG (B:s
(3Gddg jYde eG HGdbdH ef Cde hef ZQGe HCMTGFj hef SbeC(B/(3f JPcQ LjQGf HPj SdeGddg dhY CMTGFj HVGQeI dG jfWaj MQgG jheGs
(3BNQgG (B:s
(3hGdWQH GdYjS MGOj GdYjS HGdfZehhGdOj heG YbHJ ef Ndaj hGdeSdejf ef GdYQHGJ hGdYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 110s
(3eYLe GdeDdajf(B: 2 / 266s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs